Obstoj pogodbe o zaposlitvi v luči varstva zaposlitve - Kavšek, Boštjan (Delavci in delodajalci, 2020)
The present article deals with the existence of a concluded valid employment contract in the light of job protection, i.e. by limiting the admissibility of unilateral termination of an employment contract at the initiative of the employer. First, the elements and/or prerequisites for entering into a valid employment contract are presented. Consent of wills and/or an agreement to perform or provide work is an essential element of a valid employment contract. For the validity of an employment contract, the prescribed prerequisites must also be fulfilled, whereby in addition to the provisions of ZDR-1, the provisions of OZ apply mutatis mutandis in a subsidiary manner. With regard to the employment contract, we emphasized the importance of the primacy of the employment contract and the role of work commencement. We have also presented other additional conditions for job protection, which appear in comparative law (minimum period of employment, number of employees). In the second part, we introduced the institute of factual (actual) employment, where the case law extends the job protection through the presumption of the existence of an employment contract. In our view, the job protection could only be guaranteed in case of an establishment of a concluded valid employment contract.
Keywords: delovna razmerja; delovno pravo; pogodba o zaposlitvi; zaposlovanje